Rate of Cardiotoxicity in Childhood Acute Lymphoblastic Leukemia Treated with Daunorubicin Using Echocardiography and Troponin I (University Heart Journal, 2023)
Background and Aim: Acute lymphoblastic leukemia (ALL) is the commonest malignancy in childhood. Childhood ALL Survivors have a lifelong increased risk for cardiovascular morbidity and mortality compared to the general population, mainly caused by chemotherapy with daunorubicin. The aim of the study is to detect the rate of daunorubicin induced cardiotoxicity in children with acute lymphoblastic leukemia during induction phase chemotherapy.Meterials & Methods : This prospective observational study was conducted in the department of Pediatric Hematology and Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU) on 40 newly diagnosed patients of ALL aged between 1 to17.9 years who got daunorubicin during induction. Complete blood count and echocardiography were done and troponin I was measured in all patients before and after completion of induction period.Result: Of the 40 patients, 8 patients (20%) had developed cardiotoxicity evidenced by reduction of left ventricular ejection fraction (LVEF) in echocardiography. Baseline LVEF was 68.80±5.98% which was then reduced to 65.32±7.07% after induction phase of chemotherapy (p=0.023). No significant alteration of troponin I was seen (P= 0.581) between baseline and after completion of induction. Total WBC count and hemoglobin had a significant difference (P